Components characterization of total tetraploid jiaogulan (Gynostemma pentaphyllum) saponin and its cholesterol-lowering properties. (May 2016) - Liu, Jie; Li, Yanfang; Shi, Haiming; Wang, Thomas; Wu, Xianli; Sun, Xiangjun; Yu, Liangli (Lucy)
Highlights: Nine saponins, including five reported for the first time, were obtained from tetraploid jiaogulan. Total saponins (TJS) reduce plasma cholesterol by modulating intestinal gene expressions of transporters and enzymes. TJS modulated hepatic cholesterol homeostasis by promoting expression of genes for bile acids synthesis and excretion. TJS lower plasma cholesterol through suppressing intestinal absorption by inhibiting micellar solubilization in intestine. Abstract: This study characterized chemical structures of tetraploid jiaogulan saponins, and investigated their cholesterol-lowering effects and mechanisms in hamsters fed a high-fat diet (HFD). Nine saponins, including five reported for the first time, were obtained from total jiaogulan saponins (TJS) and elucidated for their chemical structures according to 2D NMR and HR-MS data. Administration of TJS effectively decreased plasma total cholesterol by 17.4% and 32.6%, triacylglycerols by 22.8% and 47.7% and LDL-C by 22.0% and 40.2%, respectively. Moreover, supplementation with TJS significantly increased faecal excretion of total cholesterol and bile acids by 43.8% and 64.4%, respectively. TJS significantly up-regulated intestinal mRNA levels of ABCG5/8, LXRα, hepatic mRNA CYP7A1 and ABCG5 in hamsters on HFD. In addition, TJS decreased cholesterol micelle solubility and suppressed cholesterol uptake in cultured Caco-2 cells. Taking together, TJS may reduce plasma cholesterol by increasing faecal cholesterol excretion and through modulation of genes involved in cholesterol absorption and metabolism.